Measurements of the neutron capture cross section of 243Am around 23.5 keV. Issue 11 (2nd November 2021) - Kodama, Yu; Katabuchi, Tatsuya; Rovira, Gerard; Kimura, Atsushi; Nakamura, Shoji; Endo, Shunsuke; Iwamoto, Nobuyuki; Iwamoto, Osamu; Hori, Jun-ichi; Shibahara, Yuji; Terada, Kazushi; Nakano, Hideto; et al.
ABSTRACT: The neutron capture cross section of 243 Am was measured by the time-of-flight method with a pulsed neutron beam from a spallation neutron source of the Japan Proton Accelerator Research Complex. An Fe neutron beam filter was used to make the incident neutron beam quasi-monoenergetic around 23.5 keV. The neutron capture γ -rays were detected with a NaI(Tl) detector. The pulse height weighting technique was employed to derive the neutron capture cross section from the pulse height spectrum. The cross section was determined relative to the capture cross section of 197 Au of JENDL-4.0. The obtained neutron capture cross section of 243 Am was 2.52  ±  0.14 b, determined with a much smaller uncertainty than those of past measurements.